Seasonal monitoring of sprint and jump performance in a soccer youth academy - Williams, C. A.; Oliver, J. L.; Faulkner, J. (International Journal of Sports Physiology and Performance, 2011)
Purpose: The aim of the study was to longitudinally assess speed and jump performance characteristics of youth football players over a 3 y period. Methods: Two hundred players across five age squads (U12-U16) from an English Football League academy participated. Sprint performance (10 and 30 m) and countermovement jump height were assessed at 6 mo intervals. Pairwise analyses determined the level of change in performance between consecutive intervals. Results: Sprint performance changes tended to be greatest during the early teenage years, with observed changes exceeding the smallest worthwhile effect (1.0% for 10 and 30 m sprints). Changes in jump performance were above the smallest worthwhile effect of 1.8% for all but one interval. Large individual variability in the magnitude of change in sprint and jump performance, perhaps due to the confounding effect of growth and maturation, revealed few significant differences across the 6 mo intervals. Cumulative changes in performance demonstrated strong linear relationships, with a yearly rate of change of 6.9% for jump height, and 3.1 and 2.7% for 10 m and 30 m sprint time respectively. The magnitude of change in performance tended not to differ from one interval to another. Conclusions: The results of this study may primarily be used to monitor and predict the rate of progression of youth football players. In addition, these results may be used as a benchmark to evaluate the effectiveness of a current training program.